Description of School Health Program in SDI Oesapa Kecil I Kupang, East Nusa Tenggara - Maria Indrawati Dairo Lede; Serlie K. A. Littik; Dominirsep Ovidius Dodo (Lontar : Journal of Community Health, 2021)
School Health Program (UKS) is the main channel for health education in schools to improve the ability to live healthily, and subsequently from healthy living behaviors, which will result in the optimal health status of students. At the time in October 2019, the implementation of UKS at SDI Oesapa Kecil I was not fully following the standards of a healthy school. This study aimed to determine the description of health education, health services, and the development of a healthy school environment in the healthy school model at SDI Oesapa Kecil I. This is a descriptive study and was carried out at SDI Oesapa Kecil I, Oesapa Barat. The research population is teachers and students in classes V and VI. This study used a probability sampling technique, namely proportionate stratified random sampling. Sample size is 71 people. The results showed not all routine activities of the school health program in the health education section were carried out, such as the use of health literacy hours, nutritious breakfast together and students brushing teeth together at school. The program for the health services section of this school also was not carried out all routine activities, such as the absence of reports on the results of health screening and periodic examinations from the health center to the school or from school to parents or guardians.